1988
DOI: 10.1111/j.1471-4159.1988.tb01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Deficiency of Thiamine on Brain Pyruvate Dehydrogenase: Enzyme Assay by Three Different Methods

Abstract: A simple and rapid method based on the NADH-linked reduction of a tetrazolium dye was described for the determination of pyruvate dehydrogenase activity in rat brain homogenates. The method (method 3) gave a value of 36.06 +/- 1.24 nmol of pyruvate utilised/min/mg of whole brain protein. This value was higher than that obtained by measurement of the rate of decarboxylation of [1-14C]pyruvate (15.10 +/- 0.88 nmol/min/mg of protein; method 1) and was comparable with the rate of transfer of acetyl groups to an ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 49 publications
4
28
0
Order By: Relevance
“…Consistent with previous investigations (Sims, 1990), the specific activities of mitochondrial en zymes measured in the present study were two-to threefold greater than values reported previously (Lai and Cooper, 1986;Mizuno et aI., 1987;Elnageh and Gaitonde, 1988) for brain mitochondria isolated using alternative preparative procedures. As the isolated mitochondrial population is likely to in clude organelles from both neuronal and glial cells, no conclusions can be reached as to the cellular location of the observed changes in the dorsolateral striatum.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with previous investigations (Sims, 1990), the specific activities of mitochondrial en zymes measured in the present study were two-to threefold greater than values reported previously (Lai and Cooper, 1986;Mizuno et aI., 1987;Elnageh and Gaitonde, 1988) for brain mitochondria isolated using alternative preparative procedures. As the isolated mitochondrial population is likely to in clude organelles from both neuronal and glial cells, no conclusions can be reached as to the cellular location of the observed changes in the dorsolateral striatum.…”
Section: Discussionsupporting
confidence: 92%
“…PDHC activity was determined spectrophotometrically by the method of Hinman and Blass (1981) with minor modifications as described by Elnageh and Gaitonde (1988). For measurements of the total activity of the PDHC, mitochondria were suspended in 250 ILl buffer containing 1 mM 2-mercaptoethanol, 1 mM EDT A, 10 mM MgCI2, 0.…”
Section: Enzyme Assaysmentioning
confidence: 99%
See 3 more Smart Citations